Two Warehouse Inventory Model for Deteriorating Items with Ramp Type Demand and Price Discount on Backorders - Chandra, S. (Journal of Scientific Research, 2021)
In this paper, a two warehouse inventory model for deteriorating items is studied with ramp type demand rate. Holding cost of rented warehouse has higher than the owned warehouse due to better preservation facilities in rented warehouse. Due to the improved services offer in rented warehouse, the deterioration rate in rented warehouse is less than deterioration rate in owned warehouse. When stock on hand is zero, the inventory manager offers a price discount to customers who are willing to backorder their demand. The study includes some features that are likely to be associated with certain types of inventory, like inventory of seasonal fruits and vegetables, newly launched fashion items, etc. The optimum ordering policy and the optimum discount offered for each backorder are determined by minimizing the total cost in a replenishment interval.